Skimming the achieved? Quantifying the fiscal incentives of the German fiscal equalization scheme and its reforms since 1970 - Yannick Bury; Lars P. Feld; Heiko Tobias Burret (Albert-Ludwigs-Universität Freiburg, Institut für Allgemeine Wirtschaftsforschung, Abteilung für Wirtschaftspolitik und Ordnungsökonomik, 2021)
Marginal rates of contribution (MRC), i.e., the rates at which additional revenues are skimmed via larger contributions or lower transfer receipts, quantify the incentives of a fiscal equalization scheme. The present paper is the first to calculate the marginal rates of contribution for the Laender (states) in the German fiscal equalization scheme for each of the 50 years since its establishment in 1970 and over five major reforms, taking into account all relevant revenues. Our results show that MRC have been at a consistently high level. Until 2019 the scheme induced an almost full skimming of additional tax revenues of recipient states. With the system's latest reform in 2020, MRC did increase further. Recipient states now face an over-skimming of additional tax revenues and thus, massive fiscal disincentives to maintain their own tax base. While these findings have been widely expected, comprehensive evidence has been missing so far.
Keywords: H71; H73; H77; H11; 330; Fiscal equalization; Marginal contribution rates; Constitutional reform